Identifikasi Kandungan Ekstrak Kayu Jati Menggunakan Py-GCMS - Fendi Fendi; Dian Kurniaty (Institut Pertanian Bogor, 2016)
Teak wood (Tectona grandis Lf.) in the form of sawdust a byproduct/waste from the furniture industry has a considerable amount and has not been utilized optimally. This study aims to determine the content of extractive teak wood (Tectona grandis Lf.). The method used is the hot water solubility. Muna's teak wood powder weighing 4,076 g soaked in distilled water as much as 100 ml glass flask, then heated in a water bath at a temperature of 100 oC for 3 hours. The content of extractive dissolved in a liquid further characterized using Py-GCMS. Results of the analysis of Py-GCMS to extract teak wood showed concentrations of some substances, such as Carbamic acid (70,70%), mono ammonium salt (CAS) Ammonium carbamate (70,70%), Acetic acid (CAS) Ethylic acid (10,52%), Acetic acid (CAS) Ethylic acid (2,35%), Acetic acid (CAS) Ethylic acid (3,26%), and Phenol (CAS) Izal (13,17%)